Efficiency tests of a twenty horse-power Avery Traction Engine no. 2116 - Carnahan, August Belmont; Barnard, Asa William; Thompson, Roger S. (My University, 1905)
Introduction: Purpose: The purpose of the following is to set forth the mechanical efficiency of the Avery traction engine No. 2116, running as a stationary engine and as a traction engine; to determine the evaporative power of the boiler under a reasonable load While being fired with Lansing coal from the Kansas Penitentiary; and to determine the draft per ton of haul over dirt and macadamized roads with an ordinary four inch wagon. The instruments used for the tests for mechanical efficiency were: Two Crosby indicators, each closely connected A Crosby disk revolution counter/ A Prony brake/ A platform scale and/ An indicator reducing motion/ To make a reliable test of an engine requires a correct application of instruments and a skillful manipulation of the same. The error of every instrument should be determined before and after the test and necessary corrections made for the same. No instrument of doubtful reading should be used under any circumstances. Ease of manipulation adds much to the accuracy with *high a reading may be made. All readings ought to be made simultaneously in order that they may harmonize. The Indicators: Of the sources of error accompanying the use of indicators we found that two above all should be sought out.
Citation: Carnahan, August Belmont, Barnard, Asa William, and Thompson, Roger S. Efficiency tests of a twenty horse-power Avery Traction Engine no. 2116. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Crosby Disk Revolution Counter; Prony Brake; Crosby Indicator; Theses